Políticas públicas municipais e gestão de fauna silvestre vitimada pelo comércio ilegal de animais: análise dos municípios paulistas que possuem CETAS e CRAS - Zambom, Maria Luiza Appoloni (Universidade Federal de São Carlos, 2018)
The present research focuses on aspects regarding the municipal management of wildlife victimized by illegal trade. Its main objective is to analyze some aspects of the public policies regarding the management of wild fauna smuggling in the 14 cities of São Paulo State where there are Wildlife Screening Centers (CETAS) or Wildlife Rehabilitation Centers (CRAS). The hypothesis is that the present public policies of the cities studied are still initials. Through a qualitative approach, the applied methodology made use of bibliographical research, search for municipal laws and documents about public policies regarding the fight against animal trafficking, and interviews with those in charge of the department of environmental affairs of each city (group 1), with the ones in charge of the CETAS / CRAS in the state of São Paulo (group 2), and also with experts in the field of study (grup 3). The main results of the research corroborate its initial hypothesis, insofar most of the municipal normative instruments found by the present study only bring municipal educational campaigns, thematic weeks and commemorative dates for the protection, defense and welfare of the animals, focusing on the domestic ones (dogs and cats). The exception is the city of São Paulo, whose laws determine that the city must curb the traffic of wild animals, implant its CETAS and CRAS, and also create the Parliamentary Group for Protection and Defense of Animals. The result of the present study suggests, therefore, that 13 of the 14 analyzed municipalities still need to develop their legal tools of fauna management. It was also noticed that the relations between the CETAS or CRAS and the department of environmental affairs of the cities are also absence of official partnerships. It is important to consider that Sao Paulo, being the capital of the State, has unique structure and administrative capacity in relation to the cities analyzed. The problem of animal smuggling is often not even took in consideration by the education actions developed by environmental agencies of the cities, and there is still a great disregard for the issue from the majority of the managers of municipal environmental departments. In its conclusion, the study proposes that a municipal model for fauna management, with a focus on fighting against animal trafficking, should involve at least the following elements: a specific section or department, preferably as part of the environmental affairs of the city and whose employees are trained; a deliberative municipal council with an equal composition of members of the local Government, organized civil society and representatives of different sectors whose interests are the protection and conservation of the fauna; a specific municipal fund with financial resources to be used to make this management viable; a CETAS or CRAS in the municipality or in nearby cities. To make all this happen, it is necessary that the state fauna management system articulates its actions with the cities.
Keywords: Fauna silvestre; Políticas públicas; CETAS; CRAS; Wild animals; Public policy; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS